Identification of Immediate and Remote Health Hazards and the Need for Health Hazard Assessment in the Nigeria Sawmill Industry - Chidozie Charles Nnaji; Udeme Udokpoh (CV. Literasi Indonesia, 2023)
This research was carried out to identify immediate and remote health hazards, including the need for health hazard assessment in the sawmill industry in Enugu State, Nigeria. A quantitative research approach was used and 300 well-structured questionnaires were directly administered to five sections of sawmill workers. Interviews and observational studies were also used to acquire data. The data was analyzed with IBM SPSS Statistics 20 software using basic percentages and inferential statistics from chi-square test analysis. The significance level was set at 0.05. Respondents in this study identified several immediate and remote health hazards, including accidents and injuries, that were linked to the various tasks they do in the sawmill. Machine operators and carpentry/furniture workers, on the other hand, were shown to be more exposed to these hazards. Asthma, dermatitis, sequoiosis, respiratory problems, heart problems, and skin disorders are among the hazards reported. Others included cuts, piercings, crushed injuries, fractures, dislocations, bruises, falls, etc. There was a significant difference in the types of ailments suffered by different categories of workers. The study also found that the total cost of fire-related losses in sawmills between 2004 and 2014 was 4.09 billion Naira. Notwithstanding the hazards and medical concerns indicated by the workers, their use of PPE was unsatisfactory. Occupational safety and health legislation, such as the Occupational Safety and Health Framework Directive, which requires employers to adopt appropriate precautionary measures to make work safer and healthier, should be implemented in all sawmills.